Nonresident Mothers - Donna Davis (EDIS, 2012)
“We read and hear stories with some frequency about “deadbeat dads” or those nonresident fathers who fail to make child support payments. The issue has prompted numerous studies and legislative action as well. But have you ever heard of a “deadbeat mom”? Not likely or rarely. This is a growing problem that has remained largely under the radar.” This 2-page Family Album Radio transcript was written by Donna Davis and published by the UF Department of Family, Youth and Community Sciences, July 2012.